Technological pedagogical academic content knowledge (TPACK+) as a novel framework for higher education teachers: development and validation - Yang, Mingxing; Yang, Wei (Springer, 2026)
This study develops and validates the technological pedagogical academic content knowledge (TPACK+) scale, an extension of the TPACK framework that incorporates academic knowledge (AK) to address the unique demands of higher education teachers. Data were collected from 303 university teachers in China and Malaysia, using exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). The EFA identified a 15-factor structure, including the original seven TPACK factors and eight new factors related to academic knowledge (academic knowledge, academic content knowledge, pedagogical academic knowledge, technological academic knowledge, pedagogical academic content knowledge, technological pedagogical academic knowledge, technological academic content knowledge, and technological pedagogical academic content knowledge). The CFA confirmed strong model fit (χ²/df = 2.028, CFI = 0.935, RMSEA = 0.058) for the new factors, with high reliability. The TPACK + framework introduces eight new factors related to academic knowledge (AK), distinguishing it from the original TPACK framework. Results indicated that the newly introduced academic knowledge-related factors emerged as distinct dimensions, confirming their conceptual independence and importance. Hence, this expanded TPACK + framework better reflects the dual responsibilities of teaching and research in higher education, providing university teachers with a more adaptive, relevant, and comprehensive knowledge structure.